A bloke's diagnose-it-yourself guide to health - Hopcroft, Keith (Oxford medical publications, 2000)
"By providing step-by-step flowcharts to self diagnosis of all the common symptoms a bloke experiences, along with advice on what to do, this book will sort him out - from the pain in his bottom to the ache in his elbow, from feeling down to not getting it up, from loss of weight to loss of sex drive, it's all here. In just a few seconds, he'll know what's wrong, whether he needs urgent help or just a couple of paracetamol. With a non-preachy, down-to-earth approach, and an emphasis on enjoying life, the book also offers some practical advice on how he can get help when he really needs it - and how he can keep partying but live to an age to make those pension contributions worthwhile."--BOOK JACKET.